2016
DOI: 10.3311/ppch.8786
|View full text |Cite
|
Sign up to set email alerts
|

Produced Water from Oil-Gas Plants: A Short Review on Challenges and Opportunities

Abstract: The produced water, which could be a complex mixture of different organic and inorganic compounds (mostly salts, minerals and oils) is a major wastewater stream generated during oil and gas production processes. Due to increase oil and gas exploration and production, especially from unconventional resources like shale oil and gas reservoirs, the volume of this effluent production is increasing around the world and its discarding to the environment is one of the global concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Produced water compound is categorized as organic substance, inorganic substance, and radionucleotide. Moreover, produced water contains some important compounds, such as dissolved and dispersed oil compounds, dissolved formation minerals, production chemical compounds, production solids, and dissolved gases [2]. Oils consist of monocyclic aromatic hydrocarbons such as benzene, toluene, ethylbenzene, and xylene (BTEX), polyaromatic hydrocarbons (PAH), and related heterocyclic aromatic compounds [3].…”
Section: Introductionmentioning
confidence: 99%
“…Produced water compound is categorized as organic substance, inorganic substance, and radionucleotide. Moreover, produced water contains some important compounds, such as dissolved and dispersed oil compounds, dissolved formation minerals, production chemical compounds, production solids, and dissolved gases [2]. Oils consist of monocyclic aromatic hydrocarbons such as benzene, toluene, ethylbenzene, and xylene (BTEX), polyaromatic hydrocarbons (PAH), and related heterocyclic aromatic compounds [3].…”
Section: Introductionmentioning
confidence: 99%
“…ONTs were hybridized with MNPs prepared by the conventional method. No ONT-MNP hybrids were formed at neutral and alkaline pH (5-12), but were formed at weak acidic pH (3)(4). ONTs aggregated tightly and produced no hybrids at strong acidic pH (1)(2)(3).…”
Section: Hybridization Of Onts With Ferromagneticmentioning
confidence: 99%
“…On the other hand, biological treatment studies have shown that rotating biological contactor (RBC) discs removed 78%-97% of COD and 95%-99% of TPH [48][49][50][51], and a membrane bioreactor (MBR) removed 96% of COD [11]. Nevertheless, new technologies have been tested, such as membrane in reverse osmosis (RO) and filtration membranes (which removed 82%-99% of COD [52][53][54][55]) and a hybrid microfiltration (MF)/ultrafiltration (UF) process (which removed 94.4%-98.8% of COD [56]).…”
Section: Introductionmentioning
confidence: 99%